Best Answer

4x +32 can be factorised as 4(x + 8). Other than that there is not much you can do with the expression.

Q: What is 4x plus 32 degrees?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x+32=-4x+16x4x+32=12x-4x -4x32=8x/8 /84=x

It is an algebraic expression in the form of: 4x+32

48-4x-13=4x+32+x First combine like terms So 48-13-4x=35-4x 4x+x+32=5x+32 Get the x by itself by subtracting the 32 from both sides 35-4x=5x+32 -32 -32 3-4x=5x +4x +4x 3=9x Divide both sides by 9 to get x by itself 3/9=x Simplify 1/3=x

x2 + 4x - 32 = (x + 8)*(x - 4)

x2+4x-32 = (x-4)(x+8) when factored

Related questions

4x+32=-4x+16x4x+32=12x-4x -4x32=8x/8 /84=x

It is an algebraic expression in the form of: 4x+32

48-4x-13=4x+32+x First combine like terms So 48-13-4x=35-4x 4x+x+32=5x+32 Get the x by itself by subtracting the 32 from both sides 35-4x=5x+32 -32 -32 3-4x=5x +4x +4x 3=9x Divide both sides by 9 to get x by itself 3/9=x Simplify 1/3=x

x2 + 4x - 32 = (x + 8)*(x - 4)

x2+4x-32 = (x-4)(x+8) when factored

1

To solve 4x+3-x=4x-32 we use the additive property of equaility and add -3 to both sidesSo 4x-x=4x-32-3Simplify this by now subtracting 4x from both sides.-x=-35 or x=35Check it.3-35=-32 so it works.

4x - 10 = -4x + 22 +4x+10=+4x +10 8x = 32 x = 4

(2x - 8)(-4x + 4) = -8x2 + 40x - 32

16x

If you mean -(x^2) - 4x + 32, then a simple way to do this is to factor out -1 first: -((x^2) + 4x - 32). Then you need simply to factorise the part inside the brackets

The discriminant is -32.